Dynamic expression of the p53 family members p63 and p73 in the mouse and human telencephalon during development and in adulthood - Hernández-Acosta, N; Cabrera-Socorro, A; Morlans, M; Delgado, F; Suárez-Solá, M; Sottocornola, R; Lu, X; González-Gómez, M; Meyer, G (2011)
p63 and p73, family members of the tumor suppressor p53, are critically involved in the life and death of mammalian cells. They display high homology and may act in concert. The p73 gene is relevant for brain development, and p73-deficient mice display important malformations of the telencephalon. In turn, p63 is essential for the development of stratified epithelia and may also play a part in neuronal survival and aging. We show here that p63 and p73 are dynamically expressed in the embryonic and adult mouse and human telencephalon. During embryonic stages, Cajal-Retzius cells derived from the cortical hem co-express p73 and p63. Comparison of the brain phenotypes of p63- and p73- deficient mice shows that only the loss of p73 function leads to the loss of Cajal-Retzius cells, whereas p63 is apparently not essential for brain development and Cajal-Retzius cell formation. In postnatal mice, p53, p63, and p73 are present in cells of the subventricular zone (SVZ) of the lateral ventricle, a site of continued neurogenesis. The neurogenetic niche is reduced in size in p73-deficient mice, and the numbers of young neurons near the ventricular wall, marked with doublecortin, Tbr1 and calretinin, are dramatically decreased, suggesting that p73 is important for SVZ proliferation. In contrast to their restricted expression during brain development, p73 and p63 are widely detected in pyramidal neurons of the adult human cortex and hippocampus at protein and mRNA levels, pointing to a role of both genes in neuronal maintenance in adulthood. © 2010 Elsevier B.V.